Regulation of inflammation and immunity in sepsis by E3 ligases - Shao, Shasha; Zhou, Daixing; Feng, Jun; Liu, Yanyan; Baturuhu,; Yin, Huimei; Zhan, Daqian (Frontiers in Endocrinology, 2023)
Sepsis is a life-threatening organ dysfunction caused by an abnormal infection-induced immune response. Despite significant advances in supportive care, sepsis remains a considerable therapeutic challenge and is the leading cause of death in the intensive care unit (ICU). Sepsis is characterized by initial hyper-inflammation and late immunosuppression. Therefore, immune-modulatory therapies have great potential for novel sepsis therapies. Ubiquitination is an essential post-translational protein modification, which has been known to be intimately involved in innate and adaptive immune responses. Several E3 ubiquitin ligases have been implicated in innate immune signaling and T-cell activation and differentiation. In this article, we review the current literature and discuss the role of E3 ligases in the regulation of immune response and their effects on the course of sepsis to provide insights into the prevention and therapy for sepsis.